Mast Cell Proteases 6 and 7 Stimulate Angiogenesis by Inducing Endothelial Cells to Release Angiogenic Factors - de Souza, Devandir Antonio (PLoS One, 2015)
Mast cell proteases are thought to be involved with tumor progression and neo-vascularization. However, their exact role is still unclear. The present study was undertaken to further elucidate the function of specific subtypes of recombinant mouse mast cell proteases (rmMCP-6 and 7) in neo-vascularization. SVEC4-10 cells were cultured on Geltrex(®) with either rmMCP-6 or 7 and tube formation was analyzed by fluorescence microscopy and scanning electron microscopy. Additionally, the capacity of these proteases to induce the release of angiogenic factors and pro and anti-angiogenic proteins was analyzed. Both rmMCP-6 and 7 were able to stimulate tube formation. Scanning electron microscopy showed that incubation with the proteases induced SVEC4-10 cells to invade the gel matrix. However, the expression and activity of metalloproteases were not altered by incubation with the mast cell proteases. Furthermore, rmMCP-6 and rmMCP-7 were able to induce the differential release of angiogenic factors from the SVEC4-10 cells. rmMCP-7 was more efficient in stimulating tube formation and release of angiogenic factors than rmMCP-6. These results suggest that the subtypes of proteases released by mast cells may influence endothelial cells during in vivo neo-vascularization.